Transthyretin Proteins Regulate Angiogenesis by Conferring Different Molecular Identities to Endothelial Cells - Nunes, Raquel J. (2014)
"This research was originally published in The Journal of Biological Chemistry. Raquel J. Nunes, et al. Transthyretin Proteins Regulate Angiogenesis by Conferring Different Molecular Identities to Endothelial Cells. Journal Name. 2013; 288:31752-31760. © the American Society for Biochemistry and Molecular Biology."